Nový textový pramen Prometheových jater - Jakub Říha (Slovo a Smysl, 2023)
This article explores a newly discovered source text for Jiří Kolář’s Prometheus’s Liver: a typescript preserved in the estate of Vítězslav Kocourek, who at the time was an editor at the Československý spisovatel publishing house. Everything suggests that this typescript was the basis for a typeset version prepared for publication in 1970. The typescript contains a number of modifications and elisions, and as such represents a key source for research on a particular phase of the history of the text.